Sex-determining region complements traditionally used in phylogenetic studies nuclear and chloroplast sequences in investigation of Aigeiros Duby and Tacamahaca Spach poplars (genus Populus L., Salicaceae) - Borkhert, Elena V.; Pushkova, Elena N.; Nasimovich, Yuri A.; Kostina, Marina V.; Vasilieva, Natalia V.; Murataev, Ramil A.; Novakovskiy, Roman O.; Dvorianinova, Ekaterina M.; Povkhova, Liubov V.; Zhernova, Daiana A.; Turba, Anastasia A.; Sigova, Elizaveta A.; et al. (Frontiers in Plant Science, 2023)
Members of the genus Populus L. play an important role in the formation of forests in the northern hemisphere and are used in urban landscaping and timber production. Populus species of closely related sections show extensive hybridization. Therefore, the systematics of the genus is rather complicated, especially for poplars of hybrid origin. We aimed to assess the efficiency of application of the sex-determining region (SDR) in addition to the nuclear and chloroplast genome loci traditionally used in phylogenetic studies of poplars to investigate relationships in sections Aigeiros Dubi and Tacamahaca Spach. Targeted deep sequencing of NTS 5S rDNA, ITS, DSH 2, DSH 5, DSH 8, DSH 12, DSH 29, 6, 15, 16, X18, trnG-psbK-psbI, rps2-rpoC2, rpoC2-rpoC1, as well as SDR and ARR17 gene was performed for 379 poplars. The SDR and ARR17 gene together with traditionally used multicopy and single-copy loci of nuclear and chloroplast DNA allowed us to obtain a clustering that is most consistent with poplar systematics based on morphological data and shed light on a number of controversial hypotheses about the origin of the studied taxa (for example, the inexpediency of separating P. koreana, P. maximowiczii, and P. suaveolens into different species). We present a scheme of relationships between species and hybrids of sections Aigeiros and Tacamahaca based on molecular-genetic, morphological, and geographical data. The geographical proximity of species and, therefore, the possibility of hybridization between them appear to be more important than the affiliation of species to the same section. We suggest that sections Aigeiros and Tacamahaca are probably primarily divided on the basis of the ecological principle (plain and mountain poplars) rather than genetically. Joint analysis of sequencing data for the SDR and chloroplast genome loci allowed us to determine the ancestors of P. × petrovskoe – P. laurifolia (female tree) × P. × canadensis (male tree), and P. × rasumovskoe – P. nigra (female tree) × P. suaveolens (male tree). Thus, the efficiency of using the SDR for the study of poplars of sections Aigeiros and Tacamahaca and the prospects of its use for the investigation of species of the genus Populus were shown.